1927
DOI: 10.3406/bulmi.1927.4019
|View full text |Cite
|
Sign up to set email alerts
|

Recherches sur la composition chimique des chlorites

Abstract: En résumé, dans ce travail, j’ai étudié plusieurs catégories de faits expérimentaux concernant les chlorites. I. J’ai précisé tout d’abord la composition chimique de plusieurs types caractéristiques appartenant aux groupes suivants : A. Prochlorites magnésiennes. __ 1. Sheridanite alumineuse de Savoie 5SiO², 3Al²O³, 8MgO, 8H²O __ 2. Leuchtenbergite de Midongy de l'Ouest et 3. Prochlorite d'Ampatsinjovana (Madagascar) 7SiO², 3Al²O³, 12MgO, 10H²O __ 4. Grochauite de Madison Cy. (Caroline du Nord) et 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1935
1935
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Smyth et al, 1997;Inoue & Kogure, 2016;Vidal et al, 2016). Among data collected in the literature, only six analyses show Fe 3 + contents of >1 a.p.f.u (Orcel, 1927;Brindley & Youell, 1953;Malysheva et al, 1977;Goodman & Bain, 1979;Kodama et al, 1982;Singer et al, 2009 in Table 2). However, these analyses would actually match other phyllosilicates, suggesting contamination issues.…”
Section: A L -F R E E D I -T R I O C Ta H E D R a L S U B S T I T U Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Smyth et al, 1997;Inoue & Kogure, 2016;Vidal et al, 2016). Among data collected in the literature, only six analyses show Fe 3 + contents of >1 a.p.f.u (Orcel, 1927;Brindley & Youell, 1953;Malysheva et al, 1977;Goodman & Bain, 1979;Kodama et al, 1982;Singer et al, 2009 in Table 2). However, these analyses would actually match other phyllosilicates, suggesting contamination issues.…”
Section: A L -F R E E D I -T R I O C Ta H E D R a L S U B S T I T U Tmentioning
confidence: 99%
“…Several methods are available to measure Fe 3+ in chlorite: chemical titration (Tschermak, 1891;Orcel, 1927;Hallimond et al, 1939;Brindley, 1951), Mössbauer (Pal et al, 1993;Aja & Dyar, 2000;Inoue et al, 2009), X-ray photoelectron spectroscopy (XPS) (Inoue et al, 2010) and micro-X-ray absorption near-edge spectroscopy (µ-XANES) (Wilke et al, 2001;Vidal et al, 2006;Rigault, 2010;Trincal et al, 2015).…”
mentioning
confidence: 99%
“…Brindley and Ali (1950) have done an excellent job of providing valuable X-ray criteria for the identification of magnesian chlorites as well as explanation of their thermal behavior. Orcel (1927) in his comprehensive differential thermal study of 28 different chlorite samples showed that (a) the departure of H20 gave different endothermic peaks for different chlorites, (b) the first endothermic reaction was generally the largest, (c) the differences in the observed intensity of thermal reaction were apparent only on the second inflection, (d) leuchtenbergite, aphrosiderite and thuringite appeared to give only one endothermic peak. Two further observations from Orcel's chlorite thermograms might well be noted: (1) a few of the samples exhibited exothermic peaks following the second endothermic inflection, and (2) thermograms for sheridanite, ripidolite and clinochlore were given where the second endothermic reaction was barely visible while thermograms for other .samples of these same species showed a second inflection nearly as large as the first.…”
Section: Literature Reviewmentioning
confidence: 99%